Migraine headache in middle age and late-life brain infarcts - Scher, Ann I; Gudmundsson, Larus S; Sigurdsson, Sigurdur; Ghambaryan, Anna; Aspelund, Thor; Eiriksdottir, Gudny; van Buchem, Mark A; Gudnason, Vilmundur; Launer, Lenore J (JAMA : the journal of the American Medical Association, 2009)
Migraine is considered to be an episodic condition with no long-term consequences. However, recent studies suggest that migraine attacks may be associated with pathologic changes in the brain, particularly in the cerebellum. To determine whether individuals not reporting headache compared with individuals reporting migraine symptoms, particularly aura, in midlife are at increased risk of late-life infarct-like lesions found on magnetic resonance imaging (MRI) without consideration of clinical symptoms. A population-based study of men and women in Reykjavik, Iceland (cohort born 1907-1935; n = 4689; 57% women) were followed up since 1967, examined, and interviewed about migraine symptoms in midlife (mean age, 51 years; range, 33-65 years). Between 2002 and 2006, more than 26 years later, brain MRIs were performed. Participants reporting headaches once or more per month were asked about migraine symptoms including nausea, unilateral location, photophobia, visual disturbance, and numbness. These individuals with headache were classified as having migraine without aura, migraine with aura, or nonmigraine headache. A comprehensive cardiovascular risk assessment was performed at both examinations. Presence of infarct-like lesions (total) and specifically located in the cortical, subcortical, and cerebellar regions. Infarct-like lesions were present in 39.3% of men and 24.6% of women. After adjusting for age, sex, and follow-up time, compared with those not reporting headaches once or more per month (n = 3243), those with midlife migraine with aura (n = 361) had an increased risk of late-life infarct-like lesions (adjusted odds ratio [OR], 1.4; 95% confidence interval [CI], 1.1-1.8) that specifically reflected an association with cerebellar lesions in women (prevalence of infarcts 23.0% for women with migraine with aura vs 14.5% for women not reporting headaches; adjusted OR, 1.9; 95% CI, 1.4-2.6 vs a 19.3% prevalence of infarcts for men with migraine with aura vs 21.3% for men not reporting headaches; adjusted OR, 1.0; 95% CI, 0.6-1.8; P<.04 for interaction by sex). Migraine without aura and nonmigraine headache were not associated with an increased risk. Migraine with aura in midlife was associated with late-life prevalence of cerebellar infarct-like lesions on MRI. This association was statistically significant only for women. This is consistent with the hypothesis that migraine with aura in midlife is associated with late-life vascular disease in the cerebellum and in women.